Large eddy simulation using the general circulation model ICON. (2nd July 2015) - Dipankar, Anurag; Stevens, Bjorn; Heinze, Rieke; Moseley, Christopher; Zängl, Günther; Giorgetta, Marco; Brdar, Slavko
Abstract: ICON (ICOsahedral Nonhydrostatic) is a unified modeling system for global numerical weather prediction (NWP) and climate studies. Validation of its dynamical core against a test suite for numerical weather forecasting has been recently published by Zängl et al. (2014). In the present work, an extension of ICON is presented that enables it to perform as a large eddy simulation (LES) model. The details of the implementation of the LES turbulence scheme in ICON are explained and test cases are performed to validate it against two standard LES models. Despite the limitations that ICON inherits from being a unified modeling system, it performs well in capturing the mean flow characteristics and the turbulent statistics of two simulated flow configurations—one being a dry convective boundary layer and the other a cumulus‐topped planetary boundary layer. Key Points: Large eddy simulation using a general circulation model ICON is presented ICON is validated against standard LES models for boundary layer simulations Despite limitations, ICON performs well compared to the standard LES models